Boron (B) and Chlorine (Cl) for Citrus Trees - Mongi Zekri; Tom Obreza (EDIS)
Since mineral nutrition is a major factor in maximizing yield of high-quality fruit, understanding the functions of mineral elements, diagnosing nutrient deficiencies, and providing needed fertilizers are essential. This 4-page fact sheet describes and discusses boron (B) and chlorine (Cl) deficiencies, functions, and recommended practices to alleviate nutritional problems. Written by Mongi Zekri and Tom Obreza, and published by the UF Department of Soil and Water Science, March 2014.